Screening of bioactive compounds of sirih leaves (Piper betle L.) as antibiofilm against the glucosyltransferase of Streptococcus mutans enzyme - Elfi Zahara; Frengki Frengki; Sheila Fadillah; Daniel (Pharmaciana, 2026)
Dental caries primarily caused by Streptococcus mutans biofilm, and the critical role of the glucosyltransferase (Gtf) enzyme in its pathogenicity necessitates the search for safer natural alternatives to conventional chemical agents like chlorhexidine. The traditional "manginang" practice utilizing betel leaf (Piper betle L.) has long been empirically associated with oral health; however, scientific evidence regarding its specific bioactive compounds and their molecular antibiofilm mechanisms remains limited. This study aims to reconstruct this tradition through in silico scientific validation by screening betel leaf bioactive compounds as S. mutans biofilm inhibitor candidates, analyzing their affinity and interactions with the Gtf enzyme (PDB ID: 3AIC), and predicting their acute toxicity profiles. The research employed an in-silico method approach using software including Molecular Operating Environment (MOE v.09) and Chimera 1.13.1, as well as the Way2Drug website, protein data bank, and protox_ii. Ligand data were first collected from literature and then converted into SMILE and 3D formats. Antibiofilm activity was determined using the QSAR technique via the Way2Drug website. Compounds with selected antibiofilm activity were subsequently analyzed for their affinity to the receptor (pdb id. 3AIC) using molecular docking. Finally, the toxicity profile of each ligand was observed to predict safety. The results indicated that 25 sirih leaf bioactive compounds possessed potential antibiofilm effects, with galactinol achieving the highest score (Pa 0.943). These compounds demonstrated strong receptor affinity, with chlorogenic acid as the strongest ligand (∆Gbinding -14.68 kcal/mol), and on average exhibited low toxicity (level IV-VI). However, only 5 of the 25 compounds were predicted to have better potential than the α-maltose control.